Modularization strategy for syngas generation in chemical looping methane reforming systems with CO2 as feedstock. Issue 8 (18th March 2017) - Kathe, Mandar; Fryer, Charles; Sandvik, Peter; Kong, Fanhe; Zhang, Yitao; Empfield, Abbey; Fan, Liang‐Shih
Abstract : This study considers a CO2 feedstock in conventional methane reforming processes and metal oxide lattice oxygen based chemical looping reforming. Lattice oxygen from iron‐titanium composite metal oxide provides the most efficient co‐utilization of CO2 with CH4 . A modularization chemical looping strategy is developed to further improve process efficiencies using a thermodynamic rationale. Modularization leverages the ability of two or more reactors operating in parallel to produce a higher quality syngas than a single reactor operating alone while offering a direct solution to scale up of multiple parallel reactor processes. Experiments conducted validate the thermodynamic simulation results. Simulation and experimental results ascertain that a cocurrent moving bed in a modularization system can operate under CO2 neutral or negative conditions. The results for a modularization process system for 7950 m 3 per day (50, 000 barrels per day) of liquid fuel indicate a ∼23% reduction of natural gas usage over baseline‐case. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3343–3360, 2017